الضغط النفسي وعلاقته بتقدير الذات لدى معلمي التربية الخاصة بمؤسسات ذوي الإحتياجات الخاصة بالوادي - عبد الستار, آية; دحدة, صبرين (University of Eloued جامعة الوادي, 2023)
Abstract : This study aims to identify the relationship between psychological stress and self-esteem among special education teachers in institutions for people with special needs in El-Oued, and to explore their level of stress and the extent of their self-esteem . The study relied on the descriptive approach, and included a sample of 43 special education teachers, including 10 males and 33 females, who were selected using a survey method. Two scales were used in order to collect the necessary data : the psychological stress scale adapted from the "Management of Stress" book prepared by "Jumma Sayed Youssef", and the self-esteem scale prepared by "Cooper Smith". Then the extracted data were processed using the Statistical Package for Social Sciences (SPSS v22) program, by applying some statistical tools . The study concluded a number of results, which are as follows : - The level of psychological stress among special education teachers is below average . - There is an inverse (negative) correlation with statistical significance between psychological stress and self-esteem among special education teachers . - There are no statistically significant differences in self-esteem due to experience
مذكرة ماستر في علوم التربية تخصص تربية خاصة تعليم مكيف
Keywords: الضغط النفسي، Stresser, Stress; تقدير الذات، Amour propre, Self-esteem